1. 3^{2} × 3^{4} = 3^{2+4} = 3^{6}
The bases are the same (both 3's), so the exponents are added. 
2. 2^{2}(2^{3}) (2^{5}) = 2^{2+3+5} = 2^{10
}The bases are the same (all 2's), so the exponents are added.

3. x^{3} • x^{5} • x^{6} = x^{3+5+6} = x^{14}
The bases are the same (all x's), so the exponents are added.

4. 3^{2} + 3^{4} ≠ 3^{2+4}
Oops!! This problem is NOT multiplication. This rule does not apply to addition.

5. 5a^{2} • 2a^{3} • a^{4} = 5 • 2 • 1 • a^{2+3+4}
= 10a^{9}
The bases are the same (all a's), so the exponents are added. Notice how the numbers in front of the bases (5, 2, and 1) are being multiplied. 
6. 3x^{2} (2x^{3} + 4) = 3x^{2} (2x^{3}) + 3x^{2} (4)
= 6x^{5} + 12x^{2}
The distributive property is applied in this problem. (Multiply each term inside the parentheses by the 3x^{2} term.)
Then the exponents in the first portion are added since their bases are the same. The numbers in front (the coefficients) are multiplied.
Remember that you cannot add 6x^{5} and 12x^{2} since they are not similar (like) terms.
